Living across the Borders: The Mobility Narratives of Romanian Immigrants in Spain - Silvia Marcu (Romanian Journal of European Affairs)
This article seeks to analyze the mobility of Romanians within Spain, taking into account the current economic crisis that is affecting labour markets in Spain and Romania, and its impact upon people. Using the perceptions of Romanians, the paper examines their experiences and their understanding of their process of mobility and return as Europeans who have a right to free circulation but limited working rights in the enlarged European Union (EU). To carry out this research, the author used the qualitative method of in-depth interviews with 80 Romanian immigrants engaged in labour mobility between the two countries. The article highlights the role played by borders in studies of mobility and suggests that migrants may have varying perceptions concerning place and mobility. By looking at immigrants’ narratives the article seeks to produce a framework that reflects the transformation of immigrants into mobile citizens within the context of the EU.